Introducing pre-service teachers to game-based learning - Hernandez, James; Ramirez, Rica (International Journal of Educational Technology and Learning, 2024)
Game-based learning has increased research and interest in teacher education and teacher pedagogy. However, there is still much to learn about how teachers understand and feel about game-based learning pedagogy in the classroom. This study utilized a quantitative research methodology to better understand the changes in beliefs and attitudes toward game-based learning of teachers before and after experiencing game-based learning opportunities first-hand. The participants in this study were ninety-six pre-service teachers enrolled in a Child Growth and Development course at a public Hispanic Serving Intitution in South Central Texas University. Findings from this study indicate that pre-service teachers are comfortable using game-based learning pedagogy prior to any game-based learning interventions. Specifically, game knowledge, game content knowledge, and game pedagogical content knowledge, had a strong positive relationship with learning opportunities, attitudes towards game-based learning and overall acceptance of digital game-based learning score. Access to game-based learning experiences significantly increased teachers’ game pedagogical knowledge, game content knowledge, and experience with games knowledge. Overall, pre-service teachers’ personal experiences with gaming and attitude towards gaming is one of the key factors that contributes to their positive attitudes towards game-based learning and their ability to see the learning opportunities games have in their future classrooms.